2012
DOI: 10.9753/icce.v33.currents.28
|View full text |Cite
|
Sign up to set email alerts
|

Fully Nonlinear Boussinesq-Type Modelling of Infragravity Wave Transformation Over a Low-Sloping Beach

Abstract: Recent field studies over low sloping beaches have shown that infragravity waves could dissipate a significant part of their energy in the inner surf zone. This phenomenon and the associated short-and long-wave transformations are not well-understood. In this paper, we assess the ability of the fully nonlinear Boussinesq-type model introduced in Bonneton et al. (2011) to reproduce short and long wave transformation in a case involving a strong infragravity wave dissipation close to the shoreline. This validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…h 0 decreases), which is due to the bore merging phenomenon. This decrease is much stronger for vN03-C3 (from 3.53 to 1.99 rad s −1 ) because large-amplitude infragravity waves favour bore merging (Tissier et al 2017). However, as for the Burgers case (see figure 4), the shape of the energy spectrum at the SW scales, ω > ω m , is not affected by low-frequency waves.…”
Section: Assessment Of the Analytical Wave Energy Spectrummentioning
confidence: 81%
See 1 more Smart Citation
“…h 0 decreases), which is due to the bore merging phenomenon. This decrease is much stronger for vN03-C3 (from 3.53 to 1.99 rad s −1 ) because large-amplitude infragravity waves favour bore merging (Tissier et al 2017). However, as for the Burgers case (see figure 4), the shape of the energy spectrum at the SW scales, ω > ω m , is not affected by low-frequency waves.…”
Section: Assessment Of the Analytical Wave Energy Spectrummentioning
confidence: 81%
“…Moreover, the time evolution of ω m is controlled in the surf zone by the wave front merging phenomenon. Tissier, Bonneton & Ruessink (2017) showed that this phenomenon is favoured by the presence of infragravity waves whose intensity depends on incident wave conditions.…”
Section: Description Of Datasetsmentioning
confidence: 99%
“…A benefit of this fully nonlinear phase‐resolving approach is that no specific parameterization is required to represent surf‐zone dynamics associated with IG waves and setup because the model appropriately accounts for momentum balances created by an irregular incident wave field (Bonneton et al, , ). Similar models have been shown to accurately represent the formation and behavior of IG waves gentle sloping beaches (Tissier et al, ) and on coral reefs (Roeber & Bricker, ; Shimozono et al, ).…”
Section: Methodsmentioning
confidence: 89%
“…The weakly-dispersive finite-difference solver for wave propagation and shoaling is locally removed in areas of wave breaking, allowing wave shape and dissipation to be solved with a finite-volume solution of the NSW equations (Popinet, 2015). Similar approaches to represent wave breaking are becoming increasingly popular in a new generation of shock-capturing GN models (Bonneton et al, 2011a;Bonneton et al, 2011b;Lannes and Marche, 2015;Popinet, 2015;Tissier et al, 2012a;Tissier et al, 2012b). In Popinet (2015)…”
Section: Wave Breakingmentioning
confidence: 99%